Answer:
a = -2 or a = -5
Step-by-step explanation:
We want
. We can subtract 2 from both sides of this equation to get
. We can factor this to get that
. When the product of two numbers is equal to zero, one of the numbers must be equal to zero. This means that either a + 2 = 0, in which case a = -2, or a + 5 = 0, in which case a = -5.
Answer:
4 ∙ (3 ∙ 6) = (4 ∙ 3) ∙ 6
Step-by-step explanation:
The associative property of multiplication states that rearranging the parentheses in an expression will not change the result, as shown.
Bro that's a lot, i don't know what the heck you are talking about.